KESEJAHTERAAN PSIKOLOGIS LANJUT USIA DI LEMBAGA KESEJAHTERAAN SOSIAL AL MARHAMAH TARAKAN - Femy R. Mia; Deetje J. Solang; Dewo A. N. Narosaputra (Program Studi Psikologi Universitas Negeri Manado, 2022)
Psychological well-being is the condition of a person who has the ability to accept himself and his life in the past. This study aims to understand and describe the psychological well-being of the elderly. Elderly is a period when a person experiences various functional declines, both physiological, psychological and social. Psychological well-being as a result of one's evaluation or assessment of himself which is an evaluation of his life experiences. This study uses a phenomenological qualitative research method. Subjects in this study amounted to two people. Sampling in this study was purposive sampling. The method used in collecting this data is observation, structured interviews and documentation. The results of this study indicate that the two advanced subjects after having various obstacles and developments that must be fulfilled can overcome these things if they fulfill the dimensions of psychological well-being. Both subjects were able to fulfill the dimensions related to their psychological well-being. . Each subject was able to accept their condition as elderly parents and overcome their bad experiences in the past.